2013
DOI: 10.1055/s-0033-1350572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnification Views on the Characterization of Microcalcifications in Digital Mammography

Abstract: !Purpose: To evaluate the additional benefit of true geometric (air-gap) magnification views for the characterization of microcalcifications in digital mammography. Materials and Methods: After ethical approval, we retrospectively reviewed patient records to identify 100 patients with suspicious microcalcifications (35 malignant, 65 benign) who had a standard digital mammography and an additional digital magnification view in the same projection within three months. All images were obtained using an amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This estimated PPV is in accordance with other studies reporting a PPV in the order of 30–50% for MC undergoing biopsy [4, 5]; therefore, it may be assumed that a typical mammography screening cohort was evaluated in this prospective analysis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This estimated PPV is in accordance with other studies reporting a PPV in the order of 30–50% for MC undergoing biopsy [4, 5]; therefore, it may be assumed that a typical mammography screening cohort was evaluated in this prospective analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Several approaches have been undertaken to improve the assessment of MC including X-ray magnification views [4, 6, 2229] and computer-aided detection with partially successful results: the contrast-limited adaptive histogram equalization (CLAHE) technique for example showed promising results for the computer-aided detection in digital mammograms with a sensitivity of 92.54% and a specificity of 92.50% [30]. However, assessment of the real 3D structure of MC remains challenging in 2D projection views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the close reading, further 12 articles were excluded and 9 articles were finally selected for inclusion: five experimental phantom studies [36][37][38][39][40] and four retrospective diagnostic test studies [41][42][43][44].…”
Section: Study Selectionmentioning
confidence: 99%
“…Diagnostic test studies [41][42][43][44] reported clinical characteristics and diagnostic accuracy data for magnification and zoom at a threshold equal to or equivalent to BIRADS ≥ 4a [48], see Table 3. The ranges of sensitivity and specificity were 85-100% and 50-57%, respectively, for magnification.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%